Progression of QRS duration: a potential surrogate marker of survival in ATTRwt amyloidosis patients - Hein, Selina; Siepen, Fabian aus dem; Zierleyn, Sonja M.; Knoll, Maximilian; Katus, Hugo; Frey, Norbert; Kristen, Arnt (Orphanet journal of rare diseases, 2025)
In wild-type transthyretin amyloidosis (ATTRwt), the deposition of transthyretin in the myocardium leads to progressive heart failure. However, little is known about the short-term natural progression of this disease and potential predictors of outcome.
Gesehen am 14.01.2026